De las bandas a las culturas juveniles - Carles Feixa (Estudios sobre las Culturas Contemporáneas)
This article is an exposition about the processes of elaboration oftheoretical concepts and methodological schemes of five ofthe princi-pal theoretical methodological paradigms thatstudygangsand juveni-le cultures in western contemporary societies. These processes oftheoretical methodological elaboration are derived from the resul-ting empirical data based on participatory observation, analysis andrellection about the conducts displayedby theadolescents as membersof a larger society.